2023
DOI: 10.1542/peds.2022-060643
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Clinical Care Practices for Child Obesity Treatment. Part II: Comorbidities

Abstract: The objective of this technical report is to provide clinicians with actionable evidence-based information upon which to make treatment decisions. In addition, this report will provide an evidence base on which to inform clinical practice guidelines for the management and treatment of overweight and obesity in children and adolescents. To this end, the goal of this report was to identify all relevant studies to answer 2 overarching key questions: (KQ1) “What are effective clinically based treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…Polygenic obesity is most commonly associated with the development of type 2 diabetes, cardiovascular disease (eg, hypertension), thrombosis, dyslipidemia, obstructive sleep apnea, increased cancer risk, anxiety and depression, polycystic ovary syndrome, bone and joint issues, and nonalcoholic fatty liver disease [ [64] , [65] , [66] , [67] , [68] ]. Critically, the risks of obesity-related comorbidities, obesity in adulthood, and premature death increase with earlier onset and increased severity of obesity, and therefore may be amplified in monogenic and syndromic obesities, which are characterized by early-onset, severe obesity [ 5 , 65 , [69] , [70] , [71] , [72] , [73] , [74] ]. Obesity onset during young adulthood can also increase the risk of cardiovascular comorbidities and mortality later in life [ 75 ].…”
Section: Morbidity Mortality and Qol In Individuals With Obesitymentioning
confidence: 99%
“…Polygenic obesity is most commonly associated with the development of type 2 diabetes, cardiovascular disease (eg, hypertension), thrombosis, dyslipidemia, obstructive sleep apnea, increased cancer risk, anxiety and depression, polycystic ovary syndrome, bone and joint issues, and nonalcoholic fatty liver disease [ [64] , [65] , [66] , [67] , [68] ]. Critically, the risks of obesity-related comorbidities, obesity in adulthood, and premature death increase with earlier onset and increased severity of obesity, and therefore may be amplified in monogenic and syndromic obesities, which are characterized by early-onset, severe obesity [ 5 , 65 , [69] , [70] , [71] , [72] , [73] , [74] ]. Obesity onset during young adulthood can also increase the risk of cardiovascular comorbidities and mortality later in life [ 75 ].…”
Section: Morbidity Mortality and Qol In Individuals With Obesitymentioning
confidence: 99%
“…Many studies have clearly shown that among children and adolescents with overweight and obesity, particularly those with central fat distribution [ 28 ], levels of insulin may be increased and dyslipidemia may occur [ 29 ]. Insulin resistance is also common and a predictor of developing diabetes mellitus type 2 during adulthood (7–25% of obese adolescents have an increased risk of developing diabetes) [ 30 ]. In our cohort, half of SMS patients were obese, and it is well-established that hyperphagia and a general sedentary lifestyle might predispose to obesity in SMS [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example of this missing link in the prevention literature, we reviewed the age ranges of study populations in the cited evidence behind four major guidelines that influence US clinical practice on screening and management of prediabetes in children and adults: American Diabetes Association Standards of Care in Diabetes, 17 US Preventive Services Taskforce (USPSTF) guidelines on screening for prediabetes in adults and children, 18 , 19 and American Academy of Pediatrics (AAP) guidelines on obesity. 20 …”
Section: The Evidence Gap For Emerging Adults: Example Of the Diabete...mentioning
confidence: 99%
“…A small number of recent young adult prevention studies have kicked off this effort, but these studies are often overlooked in guidelines. 17 , 18 , 19 , 20 This reflects a need for increased visibility and rigor, with larger, more robust studies of prevention in this age range. Conduct studies specifically focused on diabetes and CVD prevention in young adults that include 18–25 year-olds.…”
Section: Recommendationsmentioning
confidence: 99%